Effects of Vonoprazan Compared with Esomeprazole on the Healing of Artificial Postendoscopic Submucosal Dissection Ulcers: A Prospective, Multicenter, Two-Arm, Randomized Controlled Trial. (18th February 2018) - Ishii, Yasuaki; Yamada, Hiroaki; Sato, Takeshi; Sue, Soichiro; Kaneko, Hiroaki; Irie, Kuniyasu; Sasaki, Tomohiko; Tamura, Toshihide; Ikeda, Ryosuke; Fukuchi, Takehide; Kobayashi, Ryosuke; Makazu, Makomo; et al.
Abstract : Background . Vonoprazan affords more clinical benefits than proton pump inhibitors (PPIs) during the healing of gastroduodenal ulcers. However, it remains controversial whether vonoprazan is more effective than PPIs when used to heal artificial ulcers arising after endoscopic submucosal dissection (ESD). Aim . This study investigated the effects of vonoprazan compared with esomeprazole on the healing of post-ESD artificial ulcers. Methods . Sixty patients who underwent gastric ESD between May 2015 and May 2017 were randomized to treatment with vonoprazan (V group) or esomeprazole (E group) for 8 weeks. Upper endoscopy was performed at 4 and 8 weeks after ESD, and drug effects were estimated based on the ulcer healing rates and shrinkage rates. Results . Fifty-three patients were analyzed. The respective 4- and 8-week ulcer healing rates did not differ significantly between V and E groups (8.0 versus 11.5%, P = 0.669 ; 88.9 versus 84.6%, P = 0.420 ). Similarly, the respective 4- and 8-week ulcer shrinkage rates did not differ significantly between V and E groups (96.8 versus 97.5%, P = 0.656 ; 100 versus 100%, P = 0.257 ). Conclusion . The healing of artificial ulcers after ESD did not differ using vonoprazan or esomeprazole. Both vonoprazan and esomeprazole were effective when used to promote artificial ulcer healing after ESD.